Structural, Electronic, Vibrational Properties and Molecular Docking of Paracetamol: a first-principle’s Study - Khadayat, Kamalesh; Joshi, Bhawani Datt (Api Journal of Science, 2024)
Aromatic compounds are known for their biological and clinical applications. The present work explores the structural, electronic, and vibrational properties of paracetamol by DFT employing B3LYP/6-31G theory using Gaussian 09 software. To examine the equilibrium geometries, vibrational spectra, molecular electrostatic potential (MEP), lowest unoccupied molecular orbital (LUMO), highest occupied molecular orbital (HOMO), and UV-Vis spectra analysis of the tittle compound were performed. Vibrational assignments based on the potential energy distribution (PED) were made using the scaled vibrational frequencies. By using the Time Dependent DFT approach the electronic characteristics are classified. The Structure Activity Relationship has been interpreted by mapping the molecular electrostatic potential (MEP) which helps in understanding how the electronic distribution affects the molecule’s behavior and interactions, particularly its activity and reactivity. Visualizing the frontier molecular orbital in both the gas and solvent phases offers important information about the reactivity, stability, as well as various structural and physical characteristics of the title compound. Additionally, the determined HOMO and LUMO energy values indicate that a charge transfer happens inside the molecule. Further, AutoDock Vina was utilized to perform the molecular docking investigation of paracetamol against the protein CYP2E1(1EQG). The docking analysis shows a -6.6 kcal/mol favorable binding affinity with the CYP2E1(1EQG) receptor, indicating a robust interaction and promising pharmacological importance.